2018
DOI: 10.1186/s12889-018-5707-z
|View full text |Cite
|
Sign up to set email alerts
|

Lipodystrophy diagnosis in people living with HIV/AIDS: prediction and validation of sex-specific anthropometric models

Abstract: BackgroundBody composition alterations, or lipodystrophy, can lead to serious health problems in people living with HIV/AIDS (PLWHA). The objectives of this study are to predict and validate sex-specific anthropometric predictive models for the diagnosis of lipodystrophy in PLWHA.MethodsA cross-sectional design was employed to recruit 106 PLWHA (men = 65 and women = 41) in Brazil during 2013–2014. They were evaluated using dual-energy X-ray absorptiometry, and 19 regions of body perimeters and 6 skinfold thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 51 publications
(50 reference statements)
0
32
1
2
Order By: Relevance
“…There is evidence suggesting that some classes of cART, especially PIs contribute to accelerating bone demineralization, which is associated with increased frequency of osteoporosis and risk of fractures in PLWHA 7,21,22 . However, we did not observe differences between sex in "time of exposure to cART" and use of PIs 15 .…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…There is evidence suggesting that some classes of cART, especially PIs contribute to accelerating bone demineralization, which is associated with increased frequency of osteoporosis and risk of fractures in PLWHA 7,21,22 . However, we did not observe differences between sex in "time of exposure to cART" and use of PIs 15 .…”
Section: Discussioncontrasting
confidence: 86%
“…Results about the average age of the participants, self-reported race/ethnicity, time of diagnosis of HIV, time of exposure to cART, type o cART, CD4+ T lymphocytes, and viral load account were previously described 15 . Briefly, we observed homogeneity of participants among age, time of diagnosis of HIV, time of exposure to cART treatment, CD4+ T lymphocytes, and viral load account (no one PLWHA showed detectable viral load) 15 . Detailed information on body composition measured by DXA separated by sex is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The use of anthropometric indicators is advantageous, simple, of good reliability and applicable on a large scale. Authors have shown high values of positive and significant correlation between anthropometric and image methods to measure body fat distribution in patients with HIV and concluded that the anthropometric model has advanced in the field of public health, facilitating early diagnosis and better management of lipodystrophy in patients with HIV, with precision and a diagnosis prediction of 80% in this target group 23 .…”
Section: Discussionmentioning
confidence: 99%
“…SMM parameters can be obtained from dual-energy X-ray absorptiometry (DXA), bioelectrical impedance analysis, magnetic resonance imaging, computed tomography, muscle biopsy, or magnetic resonance spectroscopy (2). However, these require skilled health professionals, and are high-cost and difficult to access in the context of regular clinical practice, particularly in low-and middle-income countries (7).…”
Section: Introductionmentioning
confidence: 99%